Physico-mechanical Behaviors and Durability of Heated Fiber Concrete - Benali, Redha; Mellas, Mekki; Baheddi, Mohamed; Mansouri, Tarek; Boufarh, Rafik (Civil Engineering Journal, 2021)
The objective of the present manuscript is to describe the impact of polypropylene fibers on the behavior of heated concrete subjected to heating and cooling cycles at temperatures of 200, 450 and 600 °C respectively for six hours, through a series of experimental tests on mass loss, water absorption, porosity, compressive and tensile strength. For this purpose, mixes were prepared with a water/cement ratio with the incorporation of polypropylene fibers with a rate varying from 0.5 to 1.5%. These fibers were added in order to improve the thermal stability and to prevent the concrete from splitting. The results show that a considerable loss of strength was noticed for all tested specimens. The relative compressive strengths of the concretes containing polypropylene fibers were higher than those of the concretes without fibers. Also, a greater loss of mass of the polypropylene fibers compared to those without fibers was noticed when increasing the temperature. The flexural tensile strength of the concrete was more sensitive to elevated temperatures than the compressive strength and a rapid increase in porosity was observed for the fiber-reinforced concrete compared to the reference concrete. Furthermore, water absorption by the fibers is proportional to the fiber content of the concrete.